Nature of the magnetic order in the charge-ordered cuprate La1.48Nd0.4Sr0.12CuO4. - Christensen, N; Rønnow, H; Mesot, J; Ewings, R; Momono, N; Oda, M; Ido, M; Enderle, M; McMorrow, D; Boothroyd, A (2007)
Using polarized neutron scattering we establish that the magnetic order in La(1.48)Nd(0.4)Sr(0.12)CuO(4) is either (i) one dimensionally modulated and collinear, consistent with the stripe model or (ii) two dimensionally modulated with a novel noncollinear structure. The measurements rule out a number of alternative models characterized by 2D electronic order or 1D helical spin order. The low-energy spin excitations are found to be primarily transversely polarized relative to the stripe ordered state, consistent with conventional spin waves.